People (Symphony in the Flint Hills, 2014)
For good or for ill, people have left their imprint on the Flint Hills, in the process contributing stories that help us understand our own influence over and responsibility toward this last remnant of tallgrass prairie. Some of these people and their stories are found in the essays in this section. This is the introduction to the, "People," section of the Field Journal.
Keywords: people; indian; Osage nation; buffalo; oil; Kanza Museum; culture; landmark